Community-level group sports participation and all-cause, cardiovascular disease, and cancer mortality: a 7-year longitudinal study - Taishi Tsuji; Eisaku Okada; Masashige Saito; Satoru Kanamori; Yasuhiro Miyaguni; Masamichi Hanazato; Katsunori Kondo; Toshiyuki Ojima (BMC, 2024)
Abstract Background Community-level group sports participation is a structural aspect of social capital that can potentially impact individual health in a contextual manner. This study aimed to investigate contextual relationship between the community-level prevalence of group sports participation and the risk of all-cause, cardiovascular disease (CVD), and cancer mortality in older adults. Methods In this 7-year longitudinal cohort study, data from the Japan Gerontological Evaluation Study, a nationwide survey encompassing 43,088 functionally independent older adults residing in 311 communities, were used. Cause of death data were derived from the Japanese governmental agency, The Ministry of Health, Labour and Welfare, for secondary use. "Participation" was defined as engaging in group sports for one or more days per month. To analyze the data, a two-level survival analysis was employed, and hazard ratios (HRs) and 95% confidence intervals (CIs) were calculated. Results Among the participants, 5,711 (13.3%) deaths were identified, with 1,311 related to CVD and 2,349 to cancer. The average group sports participation rate was 28.3% (range, 10.0-52.7%). After adjusting for individual-level group sports participation and potential confounders, a higher community-level group sports participation rate was found to be significantly associated with a lower risk of both all-cause mortality (HR: 0.89, 95% CI: 0.83-0.95) and cancer mortality (HR: 0.89, 95% CI: 0.81-0.98) for every 10% point increase in the participation rate. For CVD mortality, the association became less significant in the model adjusted for all covariates (HR: 0.94, 95% CI: 0.82-1.09). Conclusions Our findings support the existence of a preventive relationship between community-level group sports participation and the occurrence of all-cause and cancer mortality among older individuals. Promoting group sports within communities holds promise as an effective population-based strategy for extending life expectancy, regardless of individual participation in these groups.